GOING PAPERLESS CONCEPT IMPLEMENTATION AT SENIOR HIGH SCHOOL IN BEKASI, INDONESIA - Lintang Meida Sofia; FIya Fauha Umaima; Bruno Rumyaru (Journal of Environmental Engineering and Waste Management, 2021)
An important reason for the rise of the paperless learning environment is that society is moving towards a green direction. At the same time, the advancement of technology and how people’s consumption of scarce resources affects digital generation and the understanding of the environment in the future have attracted more and more attention. The objective of this study is to investigate how capable, and available the students are at implementing paperless classrooms with substitutes such as the digital mode in learning activities. This quantitative descriptive research uses 108 participants as a sample through a questionnaire to collect the data. The student from Computer Network Engineering major is considered as the most suitable and related to one of the variables, namely digital literacy, where students more often use technology as learning media and solutions for reducing paper usage. The data were analysed using SPSS v 22. The results of this study found that there are significant influences from Environmental Awareness, digital literacy, and habits as factors in students’ readiness to apply this concept. The coefficient of determination shows that the Environmental Awareness (X1), Digital Literacy (X2), and Habit (X3) effected the Student’s Readiness (Y) to Implement Paperless Concept of 41.3%. The rest, 58.7% will be explained by other factors that will not be discussed in this study.